Ecological relationships among habitat type, food nutrients, parasites and hormones in wild boar Sus scrofa during winter. Issue 3 (9th March 2022) - Liu, Dongqi; Li, Zhaoyue; Hou, Zhijun; Bao, Heng; Luan, Xue; Zhang, Ping; Liang, Xin; Gong, Shuang; Tian, Yumiao; Zhang, Da; She, Wen; Yang, Feifei; et al.
Abstract : Habitat quality and parasite assembly influence wildlife health, and they are key indicators of health and survivability of wildlife populations. To investigate the potential ecological relationships among habitat type, food nutrients, parasites and hormones in wild boar Sus scrofa, we collected samples of wild boar feces and available plants in their habitat by line transects during winter. Along transects, we identified the composition of plants foraged by wild boar and measured the content of nutrients in available plants to estimate nutrient intake. We also quantified parasites and hormones in wild boar fecal samples. We compared food nutrients among different forest types and explored possible relationships among estimated nutrient intake, parasites and hormones. We found coniferous forest had positive effects on estimated fat intake and negative effects on estimated protein and fiber intake by wild boar. Furthermore, we revealed that estimated fat intake was negatively correlated with Metastrongylus elongatus parasites and positively correlated with triiodothyronine (T3). In contrast, estimated protein intake was positively correlated with M. elongatus and negatively correlated with T3. Finally, we found negative relationships between T3 concentrations and loads of Ascaris suum parasites and between cortisol (COR) and loads of Trichuris suis parasites. These insights on ecological relationships help identify potential dietary parameters in winter that could help predict and manage parasite and hormone responses for wild boar population recovery.